2005
DOI: 10.1007/s10620-005-2816-1
|View full text |Cite
|
Sign up to set email alerts
|

Rebamipide Enemas–New Effective Treatment for Patients with Corticosteroid Dependent or Resistant Ulcerative Colitis

Abstract: In this study we investigated the effect of rebamipide enema in patients with steroid-resistant and/or dependent ulcerative colitis. Rebamipide enemas were administered twice daily for a 12-week period; this treatment was further continued longer in patients who requested this. Disease activity index as reflecting the clinical condition and endoscopic index with histological grading were determined before and after the treatment period. Nine of 11 (81.8%) patients on 12-week treatment with rebamipide approved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…In addition, in the case of ulcerative colitis, it is reported [31,32] that rebamipide enema treatment is useful; however, the treatment is mainly effective in local inflammation of rectum and decending colon due to the limitation of enema technique. Using chitosan capsule, rebamipide could be first distributed in the ascending colon, and then in the transverse colon and other colon.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the case of ulcerative colitis, it is reported [31,32] that rebamipide enema treatment is useful; however, the treatment is mainly effective in local inflammation of rectum and decending colon due to the limitation of enema technique. Using chitosan capsule, rebamipide could be first distributed in the ascending colon, and then in the transverse colon and other colon.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intrarectal administration has been to be an effective route of rebamipide [5,10]. Indeed, the efficacy of rebamipide enemas have been reported [6,7]. However, the efficacy of precise mechanism of intrarectal administration of rebamipide remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that rectal administration of rebamipide suppresses colonic lesions induced by dextran sulfate sodium phosphate (DSS), and its mechanisms include radical scavenging action and increased production of mucus [5]. Furthermore, rebamipide enema is effective in patients with UC who are corticosteroid-resistant [6,7]. Experimental data suggest that rebamipide is useful for DSS-induced colitis [8,9,10], however, its precise mechanisms remain to be clarified.…”
mentioning
confidence: 99%
“…It also reduces the intestinal inflammation in both the TNBS and DSS rat models of colitis [65,66] . The first open-labelled study investigating its use included 11 patients with steroid resistant/dependant proctitis or DC [67] . Histological improvement and clinical remission in 9 patients was demonstrated after 12 wk of twice daily administration of 150 mg rebamipide in 1.5% carboxymethylcellulose at pH 6.34.…”
Section: Rebamipide Enemasmentioning
confidence: 99%